2018
DOI: 10.1016/bs.mie.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Xenon–Protein Interactions: Characterization by X-Ray Crystallography and Hyper-CEST NMR

Abstract: The physiological activity of xenon has long been recognized, though the exact nature of its interactions with biomolecules remains poorly understood. Xe is an inert noble gas, but can act as a general anesthetic, most likely by binding internal hydrophobic cavities within proteins. Understanding Xe-protein interactions, therefore, can provide crucial insight regarding the mechanism of Xe anesthesia and potentially other general anesthetic agents. Historically, Xe-protein interactions have been studied primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 84 publications
2
19
0
Order By: Relevance
“…This technique has a potential for many applications since Xe is oen used as a surrogate for O 2 to study gas binding proteins. 38,39 Signicant chemical shis have been observed in such proteins [40][41][42] (with 60-80 ppm downeld shi) or macrocyclic hosts in ternary systems that are of pharmacological interest 43,44 (ca. 100 ppm upeld shi).…”
Section: Relaxivity-derived Xe Exchange Ratesmentioning
confidence: 99%
“…This technique has a potential for many applications since Xe is oen used as a surrogate for O 2 to study gas binding proteins. 38,39 Signicant chemical shis have been observed in such proteins [40][41][42] (with 60-80 ppm downeld shi) or macrocyclic hosts in ternary systems that are of pharmacological interest 43,44 (ca. 100 ppm upeld shi).…”
Section: Relaxivity-derived Xe Exchange Ratesmentioning
confidence: 99%
“…Studies have been focused on the biologically active properties of xenon used in vivo , 7 8 9 10 in vitro , 11 12 13 14 15 and in silico , 16 17 through which detailed data on the anesthetic and analgesic properties of xenon are obtained. However, the experimental in vivo approach, where xenon can affect biomolecules by contact with the skin, is completely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] Protein-based hyper-CEST contrast agents have previously been developed for the sensitive detection of biological structures. [39][40][41] The monomeric proteins TEM-1 β-lactamase (Bla) [42][43][44] and maltose-binding protein (MBP) 45 were previously identified by our laboratory as contrast agents for 129 Xe hyper-CEST.…”
mentioning
confidence: 99%
“…Previously, we showed that the 'closed' conformation that MBP adopts upon maltose binding is required for generating hyper-CEST contrast, making MBP an ultrasensitive "smart" contrast agent for maltose detection. 45 We sought to extend these studies to other PBPs as potential 129 Xe MR contrast agents. Here, our laboratory investigated ribosebinding protein (RBP) as a hyper-CEST contrast agent for the detection and quantitation of ribose in biological fluids (Scheme 1).…”
mentioning
confidence: 99%